Fracture behavior of slag & fly ash-based geopolymer concrete in comparison with opc-based conventional concrete, including the effect of steel and hybrid fibers - Singh, Pranay; Singh, Brijesh; Ojha, P N; Trivedi, Amit; Singh, Abhishek; Pede, Chirag (Revista Ingeniería de Construcción, 2023)
The study presents an experimental investigation of the fracture behavior of hardened slag and fly ash-based alkali-activated normal and high-strength geopolymer concrete compared with conventional Ordinary Portland Cement (O.P.C.) based concrete with steel and hybrid fibers. The fracture parameters considered in the experimental investigation include fracture energy, stress intensity factor, energy release rate, and characteristic length. The study concludes that the observed differences in conventional and geopolymer concrete’s fracture and mechanical performance agree with the microstructural differences between these concrete systems reported in past literature. The slag-based geopolymer concrete is marginally inferior to the O.P.C.-based concrete, with similar compressive strength in fracture performance. Also, hybrid fiber reinforcement improves the fracture performance of geopolymer concrete more than steel fiber alone. Contrary to geopolymer concrete, steel fiber reinforced conventional concrete is superior to hybrid fiber reinforced conventional concrete in terms of fracture behavior.